Cost efficiency of principal crops in Bihar (India) – A stochastic frontier approach - SINGH, K M; AHMAD, NASIM; SINHA, D K; KUMAR, ABHAY; SINGH, R K P (The Indian Journal of Agricultural Sciences, 2020)
In the present study, an attempt has been made to test the cost efficiency of cereal crops like paddy, wheat and maize separately in the state of Bihar using Stochastic Cost Frontier model. It has been tried to determine the determinants of cost inefficiencies. The study is also aimed to know the factors affecting the cost inefficiencies in production of major cereals of the state so as to ascertain proper steps to increase cost efficiency in production. Most important observation emerged that there existed non-linear relationship between cost inefficiency and farm category. Cost inefficiency first increased with the increase of farm size then it decreased. In case of paddy mechanization could negatively affect the cost inefficiency and proportion to family labour in total labour was found positive implying increase in cost inefficiency. But in wheat, family labour showed positive value, indicating thereby increase in cost inefficiency. In case of maize, coefficient of fertilizer use was observed positive indicating increase in cost inefficiency. Coefficients of land holding size were positive in all the crops for all categories of farms. This advocated non-linear relation between farm category and cost inefficiency which showed larger farms were less cost efficient. The cost inefficiency depends on proportion of family labour, mechanization, type of seed used. The result enables to identify the determinants of cost inefficiency, which will certainly guide the state to adopt suitable policies. Farmers may be made aware about rational allocation of resources to reduce cost and make farming cost efficient.